Adequacy of recommendations for adverse event management in national and international treatment guidelines for rifampicin-susceptible tuberculosis: a systematic reviewResearch in context - William Burman; Jayne Ellis; Gila Hale; Katherine Hill (EClinicalMedicine)
Summary: Background: Adverse events during tuberculosis treatment are common and are a major challenge for patients and front-line care providers. We did a systematic review of treatment guidelines for rifampicin-susceptible tuberculosis to evaluate the adequacy of recommendations for adverse event management. Methods: We searched websites, guideline registries, PubMed, and mobile health Apps to identify treatment guidelines published from October 2004 to October 2024. We recorded the presence and evidence base for specific recommendations for management of nausea/vomiting, hepatotoxicity, skin reactions, neuropathy, visual changes, drug fever, and arthralgias. Findings: We included 47 guidelines: 25 from high-burden countries, 12 international and prominent national guidelines, and 10 non-governmental guidelines. 37 guidelines (79%) included recommendations for managing adverse events: 24 (96%) of guidelines from high-burden countries, eight (80%) of those from non-governmental organizations, and four (33%) of international and prominent national guidelines. Four recommendations had formal ratings of supporting evidence. Interpretation: International and prominent national guidelines frequently lack recommendations for adverse event management or had non-specific recommendations. Research on prevention and management of common and serious adverse events should be a priority for improving the patient’s experience and the outcomes of tuberculosis treatment. Funding: This research was supported by Wellcome Trust Clinical Grants.